An analysis of derogation used in characters conversation in game God of War 2018 - Wirana, Advent Ardha; Pradipta, Bramantya (Proceeding of Conference on Literature, Linguistic, and Cultural Studies, 2023)
Conversations could also be found in entertainment media such as movies, video games, music, and other forms of media. Character interactions in a game could significantly impact the plot, gameplay, and overall enjoyment. Dialogue that denigrated or humiliated other people or particular groups could be found in both movies and video games. The purpose of this research was to identify the kind of derogation functions used and the kind of discursive moves in the game God Of War 2018. This research used a descriptive qualitative method. The data collection was done by selecting every word that referred to the word derogation, classifying it into discursive move categories and determining the function, and then analyzing by using Critical Discourse Analysis of positive self-presentation and other negative presentations by Teun A. Van Dijk. This research showed that in the game God Of War 2018, there were nine types of discursive moves, namely actor description, authority, empathy, self-glorification, and polarization Us-them categorization, norm Expression, populism, and example or illustration utterances.